Incidence and Characteristics of Alcohol-Based Hand Sanitizer Ingestion in Florida before and during the Coronavirus Pandemic - Justin Arnold; Amira Athanasios; Diep Nguyen; Rahul Mhaskar (Western Journal of Emergency Medicine)
Introduction: Hand sanitizer use and media coverage increased throughout the coronavirus-2019 pandemic. In this study our goal was to examine and compare the incidence, demographics, and clinical outcomes of exposures to alcohol-based hand sanitizers (ABHS) before and during the COVID-19 pandemic in the state of Florida. Methods: We analyzed statewide data on all ABHS exposures in adults collected by the Florida Poison Information Network from March 1, 2015–February 28, 2020 (“pre-COVID-19” cohort) and during the COVID-19 pandemic from March 1, 2020–May 5, 2023 (“COVID-19” cohort). We performed descriptive, univariable, and multivariable analyses to assess changes in sex, age, medical outcome, and intentionality of the exposure in the pre-COVID-19 vs COVID-19 study periods, and we examined the factors associated with medical outcomes. Results: We identified 876 single-substance ingestions of ABHS, 414 in the pre-COVID-19 cohort and 462 in the COVID-19 cohort. The proportions of ABHS ingestions increased significantly during the COVID-19 pandemic in all age groups except the 25–50 age group, where it decreased. Individuals 18–24 of age and those ≥51 years showed a relative increase in both intentional and unintentional ingestions during the COVID-19 period compared to the 25–50 age group. The significant risk factors associated with more severe outcomes in exposed individuals were intentional exposures and younger age. Conclusion: Unintentional ingestions of alcohol-based hand sanitizers showed a relative increase during the COVID-19 pandemic, particularly in individuals 18–25 years of age and those ≥51. Both intentional ingestions and younger age increased the likelihood of moderate or severe outcomes. Harm reduction strategies targeted toward younger individuals and those with intentional ingestions should be considered during future pandemics.